Genetic Diversity and Population Structure of the Chinese Mitten Crab (Eriocheir sinensis) from Six Different Lakes Using Microsatellites - Shengyan Su; Jean Damascene Nsekanabo; Brian Pelekelo Munganga; Xinjin He; Jianlin Li; Fan Yu; Meiyao Wang; Yongkai Tang (Fishes, 2023)
The Chinese mitten crab (Eriocheir sinensis) is among the most important species in China and other countries, and it contributes significantly to aquaculture and meeting protein demands for the fast-growing human population. To ensure their sustainable exploitation, management, and use in aquaculture, it is imperative to know their genetic diversity. Thus, we studied the genetic diversity of six populations of Chinese mitten crabs from six different lakes in the Yangtze River’s drainage system. A total of 180 Chinese mittens crabs were collected from six lakes in China, with 30 being collected from each lake. Then, DNA was extracted using TaKaRa Dalian, genotyping was performed by the Gene Marker software for statistical analysis and the genetic parameters such as observed number of alleles (Na)were studied. A total of 87 alleles were observed in 180 individuals of six wild Eriocheir sinensis populations. The Fis results showed that six sites had negative values, and crab20 had the largest value. The results of Fit showed that the single locus had a negative value. All the Fst values among the populations were lower than 0.50, while an AMOVA analysis showed that 0.36% of the genetic variation came from among the six populations and 94.08% of the genetic variation was between individuals in a population. The six Chinese mitten crab populations showed higher genetic variability among individuals of the same population with very low genetic variability between the populations. Therefore, this illustrates that the crabs from the six lakes have similar genetic diversity and minor genetic differences among them.